Structures technology historical perspective and evolution - Noor, Ahmed Khairy (American Institute of Aeronautics and Astronautics, 1998)
This new book, drawn from the pages of Aerospace America and its predecessors, rescues the insights, concerns and dreams of dozens of structural engineers for the next generation of aerospace scientists and engineers. Written by eminent individuals in structures, this book provides accessible source material for university-level design courses in aerospace engineering.